ChemInform Abstract: A Simple Metal‐Promoted Three‐Step Access to n/5/m Angular Carbocyclic Systems. Issue 24 (23rd May 2013) - Barluenga, Jose; Alvarez‐Fernandez, Ana; Suarez‐Rodriguez, Tatiana; Suarez‐Sobrino, Angel L.; Tomas, Miguel
Abstract using a cyclopentannulation of propargylmalonates and Fischer carbenes as key step